2012
DOI: 10.1111/j.1365-3059.2011.02569.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on infection and establishment of ‘Candidatus Liberibacter americanus’ and ‘Candidatus Liberibacter asiaticus’ in citrus plants

Abstract: The objectives of this work were (i) to determine the influence of temperature on infection of citrus by 'Candidatus Liberibacter asiaticus' and 'Candidatus Liberibacter americanus', the two bacterial species associated with citrus huanglongbing (HLB) in Brazil, and (ii) to determine the influence of temperature on citrus colonization by 'Ca. L. asiaticus', which has taken over from 'Ca. L. americanus' as the predominant species in Brazil since 2008. Two experiments were carried out with graft-inoculated Valen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…L. asiaticus” can infect and spread within a plant at daytime temperatures continually as high as 32°C, but population levels of “ Ca . L. asiaticus” in citrus were lower in plants held at a continual daytime temperature of 32°C than of 27°C (Gasparoto et al., ). “ Ca .…”
Section: Resultsmentioning
confidence: 99%
“…L. asiaticus” can infect and spread within a plant at daytime temperatures continually as high as 32°C, but population levels of “ Ca . L. asiaticus” in citrus were lower in plants held at a continual daytime temperature of 32°C than of 27°C (Gasparoto et al., ). “ Ca .…”
Section: Resultsmentioning
confidence: 99%
“…Liberibacter americanus” and the high titer in “ Ca . Liberibacter asiaticus”-infected symptomatic plants might account for a competitive advantage of the latter during the natural transmission by psyllids (6, 7). Hitherto, “ Ca .…”
Section: Genome Announcementmentioning
confidence: 99%
“…They concluded that CLas infection is systemic or nearly completely systemic in the trees; however, the bacterial concentrations in different portions of the tree may be below detectible levels. Furthermore, a recent study showed that temperature influences infection and establishment of CLas and CLam in citrus plants where the highest CLas titers were observed in citrus plants maintained at 22/27°C and CLas concentrations were negatively affected by a daily temperature regime of 27/32°C (Gasparoto et al, 2012). Additionally, it was reported that continuous exposure to 40 to 42°C for a minimum of 48 h significantly reduced CLas titers or even eliminated CLas from infected citrus seedling (Hoffman et al, 2013).…”
mentioning
confidence: 99%